Generative AI: Generating Black Holes of Ethics, Reality and Culture. - Budușanu, Tudor (Caietele Echinox, 2025)
Generative AI has gained impressive popularity in the last few years and seems to have established itself as the new big disruptive tool. We have yet to see its impact on the world of literature and academia, but it is becoming ever clearer that major problems could occur if it is left unchecked and unregulated. This paper aims to seek out and analyze some of the possible endpoints of Generative AI running in its current state. While I will try to avoid engaging in the general paranoia that pervades the better part of the discourse about AI, I still believe it is imperative that a critical view of its influence is put forward and becomes part of the greater effort to make AI literacy more accessible. This paper attempts to scrutinize institutionalized perspectives on AI, deconstruct the way in which its use is being interpreted and promoted and ultimately look to prop up the legitimate concerns that researchers have already brought up.